Numerical modelling of the fatigue crack shape evolution in a shot-peened steam turbine material - You, Chao; He, B. Y.; Achintha, M.; Reed, P. A. S. (Elsevier, 2017)
In this study, the short crack initiation and growth behaviour in a notched sample under low-cycle fatigue (LCF) was investigated in a low-pressure steam turbine material. Different crack initiation mechanisms and crack shape evolution processes were experimentally observed in samples subjected to different surface treatments: polished, T0 (industrially applied shot peening process) and T1 (a less intense shot peening process). To better understand the effects of shot peening on fatigue, a 3D finite element (FE) model was developed to investigate the interaction between crack growth and the effects induced by shot peening. Firstly, residual stress redistribution caused by both mechanical loading and the presence of a crack was numerically investigated. This model was also used to successfully predict the differences in crack shape evolution between varying surface conditions, and quantified the retardation of short crack growth behaviour resulting from shot peening. Finally, the 3D model introduced in this study was compared with a previously developed 2D model with plane strain assumptions to demonstrate the limitation of the 2D model in simulating the crack growth behaviour, and to emphasise the importance of taking the 3D crack shape into account when evaluating the short crack growth behaviour.
Keywords: Shot peening; Residual stress; Short crack; Crack shape; Finite element modelling